(untitled) (Revista horizonte, 2022)
Objective: to update the knowledge about the effects of physical exercise on the memory of older adults diagnosed with a neurocognitive disorder, and to analyze what type of physical exercise provides the greatest benefits in relation to the memory of these older people through a systematic review of scientific studies published in the last five years. Method: a literature search was carried out in 8 databases. The eligibility criteria were established based on the PICOS acronym: (P) older adult over 60 years old, (I) physical training protocol, (C) older adult control group, (O) quality of the protocols, (S) randomized controlled trials published between 2014 and 2019. Results: 261 articles were identified, only 9 of which met the inclusion criteria. The most effective interventions were those of a multicomponent nature. Conclusion: Exercise interventions do generate significant benefits in the memory of older adults with neurocognitive disorders from 24 months of intervention.